Peritoneal dialysis in dogs and cats - VIȚALARU, A. B. (Journal of the Hellenic Veterinary Medical Society, 2021)
Dialysis represents the separation process of a colloidal dispersion substance from molecular dispersion particles, based on the property of certain membranes to retain only colloidal particles. In veterinary medicine, the most common use for peritoneal dialysis is the therapy of acute kidney injury, although it can be employed for removing dialyzable toxins and treating pancreatitis, electrolyte disorders and acid-base imbalances, refractory congestive heart failure and metabolic congenital disorders. Peritoneal dialysis is contraindicated in patients with peritoneal adhesions, fibrosis or abdominal malignant tumours. The ideal catheter for dialysis allows for an adequate administration and evacuation of the dialysate, it determines minimum subcutaneous losses, it minimizes infection both in the peritoneal cavity and in the subcutaneous tissue. The placement method for peritoneal dialysis catheters depends on the catheter itself, on the patient and on the approximate duration of the dialysis. In cases of extreme emergency, when the peritoneal dialysis should not be used more than 72 hours, the placement of a short-term catheter is justified. The peritoneal dialysis system is placed immediately after the peritoneal dialysis catheter is inserted and attached to a closed collection system, being carefully prepped in place with dry sterile dressings. The ideal peritoneal dialysis solution should achieve the low absorption clearance of osmotic agents, provide missing or insufficient electrolytes and nutrients, correct acid-base imbalances, inhibit growth of microorganisms, and be inert with regard to the peritoneum. When initiating peritoneal dialysis in acute kidney injury, the main goal is not to immediately normalize uraemia. The initial objectives should be to normalize the hemodynamic status of the patient and the acid-base and electrolyte imbalances, as well as to reduce uraemia to a BUN of 60-100 mg/dl and to reach a creatinine of 4.0-6.0 mg/dl in 24-48 hours. Complications of peritoneal dialysis are common, but they can be easily managed if discovered or addressed in due time. The most common complications are: peritoneal catheter obstruction, electrolyte imbalances, hypoalbuminemia and bacterial peritonitis.